Individual approach to drug correction of patients with neuropathic pain - E. Yu. Soloveva; I. P. Amelina; E. K. Plieva (Лечащий Врач)
Neuropathic pain is one of the most common complaints in outpatient clinical practice, and its relevance is associated with the difficulties that arise in the process of diagnosis and rational pharmacotherapy. In accordance with the modern classification, acute pain (lasting up to 90 days) and chronic pain are distinguished. Acute pain is a sensory reaction with subsequent involvement of emotional, motivational, vegetative and other factors that occur when the integrity of the body is violated. Chronic pain is defined as pain that continues beyond the normal healing period. According to experts in the study of pain, it is possible to speak of chronicity if the duration of the existence of pain exceeds 3 months. Understanding the pathophysiological mechanisms underlying the disruption of the processes of generation and conduction of a nociceptive signal in nerve fibers, as well as the response to control the excitability of nociceptive neurons in the structures of the spinal cord and brain in neuropathic pain, provide the key to modern therapy strategies, forming the foundation for an adequate, pathogenetically substantiated drug correction. This impact should be comprehensive and individualized. Due to the fact that neuropathic pain syndrome most often develops in patients with comorbid pathology, as well as in people of the older age group, the use of oral and injectable forms of the above drugs is significantly limited. In conditions of polypharmacy, when patients are forced to take several different drugs at the same time, priority is given to topical drugs in the treatment of this pathological condition. Today, capsaicin drugs show great promise as an effective treatment for neuropathic pain, thereby opening a new chapter in the pharmaceutical industry in the field of pain relief. Topical capsaicin, used as monotherapy or in combination with other analgesics, allows patients with a minimal risk of developing adverse events to significantly reduce the severity of neuropathic pain syndrome and, as a result, improve their quality of life.